The Linguistic Modeling of Variation in Islam: Constructing Saussure’s Concepts of Langue and Parole to Religious Studies - Lukens-Bull, Ronald; Zahn, Kristen Angelucci (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2018)
Islam has some basic set of shared symbols, beliefs, and rituals that are found in the Quran and Hadith. These form the foundations of universal Islam. But even with the “universal” foundations of Islam we find considerable debate and disagreement. Dealing with the diversity in Islam, we will develop our model, especially through the more complete linguistic analogies. The core of our model borrows Saussure’s concepts of langue (language as a system) and parole (speech acts) and applied it to religion. The transcendent form of a religion, which is parallel to langue, is an ideal form in the minds and hearts of believers. The expressed form, which is analogous to parole, includes interpretations, discourse, debates, rituals, and daily life of believers. The aim of this paper is more to elucidate an analytical model than to make declarative statements about the nature of religion. We argue that a fuller linguistic analogy moves us further in our understanding of this relationship. The results of the analysis show that linguistic modeling of variation in Islam applied through several ways, there are: (1) dialects and local religious practice (2) the transcendent and the expressed as parallels to Saussure’s langue and parole (3) linguistic analogies (4) myth, doctrine, and grammar (4) syntax, Islam and ritual and (5) creoles and pidgins.